Crossing Boundaries: Mobilizing Faith, Diversity, and Dialogue (American Journal of Islam and Society, 2008)
On 24-25 October 2008, the thirty-seventh annual conference of theAssociation of Muslim Social Scientists of North America (AMSS) washeld at the Harvard Divinity School, thanks to the efforts of the late Dr.Louis Cantori (an AMSS board member) and the gracious support of DeanWilliam Graham. Given the expanding role of religion in American foreignpolicy and public life, the conference’s seven panels were structured aroundfinding common ground in a religiously pluralistic world, healing inter-religiousand intra-religious rifts, and using religion to promote (or at least mitigate)international conflicts.AliA. Mazrui (Binghamton University, andAMSS President) welcomedthe audience and spoke of how America, the world’s “first and only universalcountry,” has not always welcomed non-Anglo/non-Christian immigrants.He contended that the country might be in the process of accommodatingIslam, as witnessed by the Clinton administration’s hosting of iftar dinnersand the Bush administration’s extension of Ramadan greetings to the MuslimAmerican community ...